A Novel Role for CD46 in Wound Repair - Cardone, John; Al Shouli, Samia; Kemper, Claudia (Frontiers in Immunology, 2011)
The intestinal epithelium not only provides a vital physical barrier between the host and environment but is also required for uptake of nutrients and the induction of tolerance against commensals. Deregulation of any of these functions leads to several disease states including chronic infection, inflammatory bowel disease and cancer. Here, we describe a novel role for the complement regulator CD46 in the regulation of intestinal epithelial cell barrier function. We found that CD46 directly interacts in intestinal epithelial cells with the cytoplasmic kinase SPAK and with transmembrane E-cadherin, both proteins necessary for epithelial cell junction and barrier formation. Further, CD46 activation on Caco-2 cells induced rapid and significant decrease in transepithelial resistance with concomitant increase in paracellular permeability. Importantly, though CD46 activation of intestinal epithelial cell layers allowed for increased transgression of pathogenic E. coli, it also increased epithelial cell proliferation and accelerated wound repair. These data suggest a previously unappreciated role for CD46 in the maintenance of epithelial cell barrier integrity as well as barrier repair. However, this role for CD46 as ‘gate keeper’ of the epithelium could also provide reason as to why so many pathogens bind to CD46 as such event would facilitate infection.